Lethal cardiac amyloidosis: Modification of the Congo Red technique on a forensic case. (August 2018) - Rancati, A.; Andreola, S.; Bailo, P.; Boracchi, M.; Fociani, P.; Gentile, G.; Zoja, R.
Highlights: Discrimination amyloid. Modification Congo Red staining to evaluate amyloid deposition. Determination of amyloid on cadaveric heart. Abstract: Congo Red staining is usually used in diagnosing amyloidosis, a pathology characterized by the storage of abnormal proteins in several human organs. When assessed on samples fixated in formalin and embended in paraffin, this staining can undergo several artefacts, causing diagnostic and interpretative difficulties due to its weak stainability and a consequent reduced visibility of the amyloid. These complications, in time, requested several variations of this staining technique, especially in clinical practice, while in the forensic field no protocols has ever been adapted to cadaveric samples, a material that is already characteristically burdened by a peculiar stainability. In our work, studying a sudden death caused by cardiac amyloidosis and diagnosed only with post-mortem exams, we present a modified Congo Red staining used with the purpose to demonstrate amyloid in cadaveric material after the unsuccessfully use of all standard protocols.